MANAGEMENT OF CHRONIC LYMPHADENOPATHY WITH POOR ORAL HYGIENE IN CHILDREN (CASE REPORT) - Renie Kumala Dewi (FKG Unlam, 2020)
ABSTRACTBackground. Lymphadenopathy is a common clinical feeding an anomaly in the size and consistency of lymph nodes. Local bacterial infection causes cervical adenopathy when the lymph nodes responded to local infection. Cervical lymphadenopathy is a common problems in pediatric. Lymph node with more than 10 mm diameter is usually considered abnormal. Lymph node enlargement caused by a chronic infection is known as chronic lymphadenopathy. Objectives. Discovery management of chronic lymphadenopathy in children with poor oral hygiene.Case. A 9-year-old boy came to Pediatric Dentistry Specialist Gusti Hasan Aman Dental Hospital with his parents with a complaint of pain in his right tooth posterior mandible for the last week. The patient had received medication, however the pain still existed. Extraoral examination revealed symmetrical face, a node on the middle neck sizing 30 mm in diameter for 4 years. The lump was treated several times with no progress in size. Intraoral examination revealed a cavity in posterior lower left tooth and painful in the last 5 days without any treatment. Plaque score showed poor oral hygiene.Case Management. Based on extraoral examination, the nodule on the neck reduced in size from 30 mm to 7 mm after treatment with antibiotic, anti-inflammatory medication, dental care and control periodic for oral hygiene management. Conclusion. Early detection and accurate lymphadenopathy diagnosis is important for successful therapy. Oral hygiene improvement can help in the healing process of chronic lymphadenopathy which occurred for 4 years. Keyword: Limphadenophaty chronic, Oral hygiene, Staphylococcus aureus